DOI: 10.4995/thesis/10251/160042
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la materia prima y el proceso secado-maduración sobre la calidad del jamón curado

Abstract: RESUMENdel sistema de secado (ventana abierta o cámara), evaluando los parámetros que permiten clasificar las diferentes variables.Para ello se analizan un total de 36 jamones de cerdo blanco, tomando 12 de cada una de las procedencias objeto de estudio (convencional, ecológico y DOP Teruel), destinando 6 jamones de cada una para el secado natural y otros 6 para el secado en cámara siguiendo el mismo proceso de obtención de jamón curado para las tres procedencias, excepto la no adición de sales nítricas, en el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 155 publications
(295 reference statements)
0
1
0
Order By: Relevance
“…According to [ 59 ] the characterization of the color is achieved by means of the coordinates of L*, a* and b*, but the main purpose in the measurements of the color is the objective determination of their differences through the parameters of chroma (C*) and of the tone (h*). Our results showed that the addition of saffron gives a greater C* and tone to the ham slices, reaching significant differences among groups at 28 days in both parameters and at the end of experiment in hue.Authors such as [ 60 ] have studied the chroma and hue in Spanish saffron and dry-cured Duroc ham [ 61 ], but there are not previous references which had studied the color parameters of dry-cured ham flavored with this spice.…”
Section: Discussionmentioning
confidence: 99%
“…According to [ 59 ] the characterization of the color is achieved by means of the coordinates of L*, a* and b*, but the main purpose in the measurements of the color is the objective determination of their differences through the parameters of chroma (C*) and of the tone (h*). Our results showed that the addition of saffron gives a greater C* and tone to the ham slices, reaching significant differences among groups at 28 days in both parameters and at the end of experiment in hue.Authors such as [ 60 ] have studied the chroma and hue in Spanish saffron and dry-cured Duroc ham [ 61 ], but there are not previous references which had studied the color parameters of dry-cured ham flavored with this spice.…”
Section: Discussionmentioning
confidence: 99%